Electrocatalytic Reduction of CO2 at Au Nanoparticle Electrodes: Effects of Interfacial Chemistry on Reduction Behavior. Issue 12 (12th September 2015) - Andrews, Evan; Katla, Sai; Kumar, Challa; Patterson, Matthew; Sprunger, Phillip; Flake, John
Abstract : Nanoscale Au electrocatalysts demonstrate the extraordinary ability to reduce CO2 at low overpotentials with high selectivity to CO. Here, we investigate the role of surface chemistry on CO2 reduction behavior using Au25 and 5 nm Au nanoparticles. Onset potentials for CO2 reduction at Au25 nanoparticles in Nafion binders are shifted anodically by 190 mV while the hydrogen evolution reaction is shifted cathodically by 300 mV relative to Au foil. The net effect of this beneficial separation in onset potentials is relatively high Faradayic efficiencies for CO (90% at 0.8 V versus RHE) at high current densities. Experimental results show Faradayic efficiencies for CO are greatest using electrodes made with Nafion-immobilized Au25 nanoparticles. Likewise, CO2 reduction onset potential shifts are greater for smaller nanoparticles and when Nafion binders are used instead of (sulfonate-free) polyvinylidene fluoride. X-ray photoelectron spectroscopy analysis reveals Au nanoparticles may react with the sulfonates of Nafion binders. The results suggest sulfonate interfaces may alter the binding energies of key species or lead to favorable reconstructions, either of which ultimately results in remarkable improvements in Faradayic efficiencies relative to Au foil electrodes.